2012
DOI: 10.1177/000313481207800433
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Repair of Giant Paraesophageal Hernia with Synthetic Mesh: 45 Consecutive Cases

Abstract: Giant paraesophageal hernias (PEHs) are associated with progression of symptoms in up to 45 per cent of patients. Recently, many series have reported that laparoscopic repair of PEH is technically feasible, effective, and safe. A retrospective review of the University of Athens tertiary care hospitals patient database and the patient medical records identified 45 patients who underwent elective repair of a giant PEH between 2002 and 2009. Elective laparoscopic repair of a giant PEH was attempted in 45 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(26 reference statements)
0
3
0
3
Order By: Relevance
“…GPEH was defined by the presence of [me]30% of the stomach in the thoracic cavity. 6 During the study period, some laparoscopic cases were performed. The criteria that determined whether the procedure was laparoscopic or robotic were influenced by 3 main factors: (1) preference of the patient, (2) preference of the surgeon, (3) and availability of the robotic system.…”
Section: Methodsmentioning
confidence: 99%
“…GPEH was defined by the presence of [me]30% of the stomach in the thoracic cavity. 6 During the study period, some laparoscopic cases were performed. The criteria that determined whether the procedure was laparoscopic or robotic were influenced by 3 main factors: (1) preference of the patient, (2) preference of the surgeon, (3) and availability of the robotic system.…”
Section: Methodsmentioning
confidence: 99%
“…In selected series, gastric or esophageal perforations after laparoscopic paraesophageal hiatal hernia repair have been reported to range from 0 to 4.3 per cent (Table 2). [4][5][6][7][8][9][10][11][12] In a study of 108 patients, Oeschlager reported a perforation rate of 3.8 per cent. 11 The largest experience of laparoscopic hiatal hernia repair to date was reported by Luketich et al 4 Their study demonstrated a perforation rate of 2.5 per cent; however, a large proportion of their cases were performed in conjunction with a Collis gastroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Perioperative mortality ranged between 0 and 2.2 per cent and early reoperation ranged from 0 to 4.9 per cent. [4][5][6][7][8][9][10][11][12] In summary, laparoscopic paraesophageal hiatal hernia repair is safe, associated with a short length of stay, low perioperative morbidity, and no mortality. The use of bioabsorbable mesh appears to be acceptable in reducing the rate of hiatal hernia recurrence; however, longer follow-up is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Эти конструкции были созданы для лапароскопической интраперитонеальной пластики вентральных грыж. Рядом авторов они были применены в пластике больших и гигантских грыж пищеводного отверстия диафрагмы, причем с методикой onlay [1,2,11,12]. В опросе C. T. Frantzides и соавт.…”
Section: политетрафторэтиленовые имплантатыunclassified
“…В исследовании G. Staropoulos и соавт. у 45 пациентов частота анатомических рецидивов составила 2,2% [12].…”
Section: политетрафторэтиленовые имплантатыunclassified